2002
DOI: 10.1097/00004694-200203000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Treatment of the severely traumatized or mangled lower extremity poses significant challenges. The Mangled Extremity Severity Score (MESS) is a scale that uses objective criteria to assist with acute management decisions. Most research on the MESS has been in adults or combined series with few children. The study was performed to investigate the MESS in children exclusively. The MESS was applied retrospectively to 36 patients with grades IIIB and IIIC open lower extremity fractures collected from two level 1 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Behdad et al [ 20 ] evaluated 200 children with lower extremity long bone open fracture using MESS score, the Authors described a sensitivity of 73 % and a specificity of 54 % for a MESS ≥ 6.5. Fagelman et al [ 25 ] described an accurate prediction of 93 % when MESS is applied to grade III lower extremity fracture in children. Mommsen et al [ 26 ] analyzed 27 lower extremities in children.…”
Section: Resultsmentioning
confidence: 99%
“…Behdad et al [ 20 ] evaluated 200 children with lower extremity long bone open fracture using MESS score, the Authors described a sensitivity of 73 % and a specificity of 54 % for a MESS ≥ 6.5. Fagelman et al [ 25 ] described an accurate prediction of 93 % when MESS is applied to grade III lower extremity fracture in children. Mommsen et al [ 26 ] analyzed 27 lower extremities in children.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, among the patients subjected to amputation, 75% of their fractures were classified as type IIIC and 25% as type IIIB of Gustilo and Anderson. Fagelman et al 16 evaluated the correlation between fractures of Gustilo and Anderson types IIIB and IIIC and the MESS index for exposed fractures of the lower limbs and found results that significantly predicted treatment, for 93%. On the other hand, Sheean et al 17 did not find any significant difference in MESS values between amputees and patients whose limbs were salvaged.…”
Section: Discussionmentioning
confidence: 99%
“…The criteria for indicators such as the MESS score and the fracture classification need to be carefully analyzed so that the limb salvage can be done in an effective manner and so that amputation is done in precisely selected cases. 15 , 16 …”
Section: Discussionmentioning
confidence: 99%
“…Few data on paediatric injuries are available. Besides some reviews of paediatric open fractures [13-16], there is one retrospective investigation focussing on the relevance of the MESS in 36 children with grade IIIB and IIIC open lower extremity fractures [17]. Fagelman et al reported a limb salvage of 28.6% in patients with a MESS ≥ 7 and 89.7% in patients with a MESS < 7, respectively [17].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the available research on the MESS deals with adults, and only few data on paediatric injuries exist. Despite some reviews of paediatric open fractures indicating superior outcome in children compared to adults [13-16], there is only one retrospective study investigating the applicability of the MESS to children [17]. In the present study, besides epidemiology, diagnostics, therapeutic options and outcome of paediatric extremity arterial injuries, we investigated the prognostic value of MESS in children in order to contribute some valuable evidence to this issue.…”
Section: Introductionmentioning
confidence: 99%